2020
DOI: 10.21203/rs.3.rs-33432/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers and facilitators for transitioning of young people from adolescent clinics to adult ART clinics in Uganda: Unintended consequences of successful adolescent ART clinics

Abstract: BackgroundThere is a growing number of adolescents and young adults with HIV who require transfer of care from pediatric/ adolescent clinics to adult ART clinic. Currently, adolescents are largely in the care of pediatricians; but as they grow, they transition to adult HIV clinics. The purpose of this study was to explore the facilitators and barriers of transitioning among adolescents from adolescent clinics to adult ART clinics.MethodAn explorative qualitative approach was utilised for this study. Eighteen f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…As in our study, adolescents considered that PSWs were approachable and could easily relate to the SRH issues they experienced unlike older providers. Other studies have also shown the importance of friendly and approachable service providers in delivering adolescent friendly SRH services [35][36][37]. Similar to our study, adolescents in the other Zambian study preferred to access services from providers of the same sex as them [29].…”
Section: Discussionsupporting
confidence: 86%
“…As in our study, adolescents considered that PSWs were approachable and could easily relate to the SRH issues they experienced unlike older providers. Other studies have also shown the importance of friendly and approachable service providers in delivering adolescent friendly SRH services [35][36][37]. Similar to our study, adolescents in the other Zambian study preferred to access services from providers of the same sex as them [29].…”
Section: Discussionsupporting
confidence: 86%
“…The Silences Framework [ 13 ] guided data analysis as described in another paper [ 15 ]. This framework asserts that reality is not objective or fixed, but rather, human beings script the social world at a particular time in a given context [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Jonsen et al [ 15 ] have described an approach to clinical ethical case analysis known as the “four-quadrant” approach [ 16 , 17 ]. This framework relies on Beauchamp and Childress’s four principles ethics framework [ 18 ].…”
Section: Methodsmentioning
confidence: 99%